2020
DOI: 10.3390/nu12103073
|View full text |Cite
|
Sign up to set email alerts
|

What Was First, Obesity or Inflammatory Bowel Disease? What Does the Gut Microbiota Have to Do with It?

Abstract: A sedentary lifestyle and inadequate nutrition often leads to disturbances in intestinal homeostasis, which may predispose people to excess body weight and metabolic syndrome. Obesity is frequently observed in patients with inflammatory bowel diseases (IBD), similar to the general population. Obesity may exert a negative effect on the course of IBD as well as reduce the response to treatment. Moreover, it may also be an additional risk factor for vein thromboembolism during the flare. In both obesity and IBD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 139 publications
(144 reference statements)
0
13
0
2
Order By: Relevance
“…Obesity is characterized by weight gain above normal ranges—body mass index (BMI) ≥ 30 kg/m 2 ; overweight is defined as BMI ≥ 25 kg/m 2 . IBD is often associated with underweight (BMI < 18 kg/m 2 ); however, numerous studies find overweight and obesity also common in UC/CD patients [ 5 ]. Overweight may be present in 20–40% of IBD patients in Western countries, while obesity may affect about 15–40% of this population [ 6 ].…”
Section: Obesity and Ibdmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity is characterized by weight gain above normal ranges—body mass index (BMI) ≥ 30 kg/m 2 ; overweight is defined as BMI ≥ 25 kg/m 2 . IBD is often associated with underweight (BMI < 18 kg/m 2 ); however, numerous studies find overweight and obesity also common in UC/CD patients [ 5 ]. Overweight may be present in 20–40% of IBD patients in Western countries, while obesity may affect about 15–40% of this population [ 6 ].…”
Section: Obesity and Ibdmentioning
confidence: 99%
“…There are data suggesting that obesity does influence the efficacy of specific drugs commonly used to treat IBD. It is associated with the rapid clearance of biologic agents that could result in low trough concentrations and in suboptimal response to biological therapy [ 5 , 6 ]. A reduction in clinical outcome and lower trough levels in response to infliximab [ 28 ] and adalimumab [ 29 ] have been reported.…”
Section: Obesity and Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, obesity induces variations in the colonic microbiome that may predispose the patient to diverticulitis. Obesity and diverticulitis are associated with alterations in gut microbiota (such as an increased ratio of Firmicutes to Bacteroidetes) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that the gut microbiota affects normal physiological and biochemical functions and is associated with a variety of diseases, such as liver disease, cancer, and especially IBD [ 3 , 14 , 15 ]. In a study on IBD, the composition and function of the gut microbiota of patients with IBD were found to be modified, which may result in the impairment of gut physiological function [ 16 ].…”
Section: Introductionmentioning
confidence: 99%